2014
DOI: 10.1093/mnras/stu1055
|View full text |Cite
|
Sign up to set email alerts
|

The outer halo globular cluster system of M31 – II. Kinematics

Abstract: We present a detailed kinematic analysis of the outer halo globular cluster system of the Andromeda galaxy (M31). Our basis for this is a set of new spectroscopic observations for 78 clusters lying at projected distances between R proj ∼ 20-140 kpc from the M31 centre. These are largely drawn from the recent PAndAS globular cluster catalogue; 63 of our targets have no previous velocity data. Via a Bayesian maximum likelihood analysis we find that globular clusters with R proj > 30 kpc exhibit coherent rotation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
224
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(244 citation statements)
references
References 115 publications
20
224
0
Order By: Relevance
“…So far, seven GCs are discovered along the NWS, and five (PAndAS-04, 09, 10, 11 and 12) of them show a clear correlation of their galactocentric radial velocities with projected radii from M31's centre (see table 4 and figure 11 of Veljanoski et al 2014). In this paper, we assume that these five GCs initially inhabited the progenitor of the NWS and still have the same orbital motion as the NWS.…”
Section: Model and Assumptionmentioning
confidence: 89%
See 2 more Smart Citations
“…So far, seven GCs are discovered along the NWS, and five (PAndAS-04, 09, 10, 11 and 12) of them show a clear correlation of their galactocentric radial velocities with projected radii from M31's centre (see table 4 and figure 11 of Veljanoski et al 2014). In this paper, we assume that these five GCs initially inhabited the progenitor of the NWS and still have the same orbital motion as the NWS.…”
Section: Model and Assumptionmentioning
confidence: 89%
“…Panels (b) and (e) show the simulated LOS velocities. Red circles are the observed velocities of the GCs Veljanoski et al (2014). The spatial distribution of the particles is shown in panels (c) and (f).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fardal et al 2013;Cautun et al 2014a,b;González, Kravtsov & Gnedin 2014;Piffl et al 2014;Veljanoski et al 2014, for a compilation of other measurements and discussions of systematic effects see Courteau et al 2014;Wang et al 2015). This results in 2849 MS-II haloes and in 63 COCO haloes in the required mass range.…”
Section: Data a N D S A M P L E S E L E C T I O Nmentioning
confidence: 94%
“…Mackey et al (2010) found ∼80% of the GCs to preferentially project onto the various stellar overdensities, suggesting that these objects were brought into the M 31 system by accreted dwarf galaxies, an observation which supports hierarchical formation models. Recent kinematic studies of the M 31 outer halo GC system (Veljanoski et al 2013(Veljanoski et al , 2014 have found various velocity correlations or clustering exhibited by GCs that project along particular stellar debris features. This not only supports the accretion hypothesis but also highlights the power of using GCs as tracers of accretion events.…”
Section: Introductionmentioning
confidence: 99%